2021
DOI: 10.3390/medicina57030260
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and Induced Tumors in Germ-Free Animals: A General Review

Abstract: Cancer, bacteria, and immunity relationships are much-debated topics in the last decade. Microbiome′s importance for metabolic and immunologic modulation of the organism adaptation and responses has become progressively evident, and models to study these relationships, especially about carcinogenesis, have acquired primary importance. The availability of germ-free (GF) animals, i.e., animals born and maintained under completely sterile conditions avoiding the microbiome development offers a unique tool to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…However, experiments with germ-free mice and rats revealed the tumor-promoting effects of the gut microbiome. Animals with an intact gut microbiome had more spontaneous, genetically-induced, and carcinogen-induced tumors compared to germ-free counterparts in various organs including the lung (Schreiber et al, 1972), liver (Dapito et al, 2012;Yoshimoto et al, 2013), skin (Sacksteder, 1976), colon (Grivennikov et al, 2012), and mammary gland (Mishra et al, 2021). Additionally, gut dysbiosis induced by obesity was associated with enhanced tumor growth and significant loss of gut microbial diversity in a murine triple-negative breast cancer (TNBC) model (Hossain et al, 2021).…”
Section: Gut Microbiome Alterations and Breast Carcinogenesismentioning
confidence: 99%
“…However, experiments with germ-free mice and rats revealed the tumor-promoting effects of the gut microbiome. Animals with an intact gut microbiome had more spontaneous, genetically-induced, and carcinogen-induced tumors compared to germ-free counterparts in various organs including the lung (Schreiber et al, 1972), liver (Dapito et al, 2012;Yoshimoto et al, 2013), skin (Sacksteder, 1976), colon (Grivennikov et al, 2012), and mammary gland (Mishra et al, 2021). Additionally, gut dysbiosis induced by obesity was associated with enhanced tumor growth and significant loss of gut microbial diversity in a murine triple-negative breast cancer (TNBC) model (Hossain et al, 2021).…”
Section: Gut Microbiome Alterations and Breast Carcinogenesismentioning
confidence: 99%
“…Accumulating evidence sheds light on the association of microbiota with cancer initiation and progression, including the studies conducted on germ-free and gnotobiotic animals (i.e., animals born and raised under aseptic conditions and colonized with specific microorganisms) and their comparison with their conventional counterparts, which presented convincing evidence for microbiota's involvement in tumor induction and the establishment of local and systemic immune responses [ 36 , 37 ]. In some of these investigations, researchers found a higher frequency of liver cancer, a lower incidence of small intestinal polyposis, and little or no difference in the occurrence of mammary tumors in germ-free mice [ 38 – 40 ].…”
Section: Association Between Microbiome and Cancer Developmentmentioning
confidence: 99%
“…In some of these investigations, researchers found a higher frequency of liver cancer, a lower incidence of small intestinal polyposis, and little or no difference in the occurrence of mammary tumors in germ-free mice [ 38 – 40 ]. Moreover, the incidence of tumors induced by carcinogens in germ-free (GF) and conventional (CV) animals exhibited contradictory results, which could be related to differences in animal strains, tumor induction protocol (including type, dose, and route of administration of carcinogen), and organs involved in carcinogenesis [ 37 , 41 – 45 ].…”
Section: Association Between Microbiome and Cancer Developmentmentioning
confidence: 99%
“…Multiple similar studies have demonstrated that microorganisms are present within different types of tumors and these intratumoral microorganisms are heterogeneous. Researchers have proven the involvement of microbiota in tumor development and the creation of local and systemic immune responses by working with sterile humanized mice as biomicrobial models [ 8 , 9 ]. The vast majority of microorganisms use nucleic acid (DNA or RNA) as their genetic material, and the genes of microorganisms also have their specific species characteristics.…”
Section: Introductionmentioning
confidence: 99%